2018
DOI: 10.18805/ijar.b-834
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of microRNAs in white and black coated yak

Abstract: In this study, we used high-throughput technology to provide the first transcriptome dataset for differentially expressed miRNA in mixed pools of dermis tissue from black- and white-coated yak to research the possible molecular mechanisms of yak coat pigmentation. In this study, 92,636,002 and 95,917,842 clear reads were generated through Illumina paired-end sequencing. A total of 78 differentially expressed miRNAs (DEMs) were identified, including 59 upregulated and 19 downregulated miRNAs in the mixed pools … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…MiRNAs regulate more than 30% of chromosomes in the human genome (Bartel, 2004). The research on miRNA has gradually expanded from human and model animals to other common livestock (Basang et al, 2018), new miRNAs were often reported (Chang et al, 2018). As one of the most important regulators, miRNA can affect cell proliferation, apoptosis, adhesion, angiogenesis and migration directly or indirectly (Chen et al, 2016;Paramasivam et al, 2017) To achieve a mutually acceptable state between the maternal uterus and the embryo in the process of implantation, it is necessary to regulate many related genes to make the maternal body reach an optimally receptive state.…”
Section: Introductionmentioning
confidence: 99%
“…MiRNAs regulate more than 30% of chromosomes in the human genome (Bartel, 2004). The research on miRNA has gradually expanded from human and model animals to other common livestock (Basang et al, 2018), new miRNAs were often reported (Chang et al, 2018). As one of the most important regulators, miRNA can affect cell proliferation, apoptosis, adhesion, angiogenesis and migration directly or indirectly (Chen et al, 2016;Paramasivam et al, 2017) To achieve a mutually acceptable state between the maternal uterus and the embryo in the process of implantation, it is necessary to regulate many related genes to make the maternal body reach an optimally receptive state.…”
Section: Introductionmentioning
confidence: 99%